1992
DOI: 10.1037/0882-7974.7.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Everyday memory performance across the life span: Effects of age and noncognitive individual differences.

Abstract: Gerontologists have long been concerned with the impact of individual-difference factors on memory. This study used a large sample (N = 2,495) of adult volunteers aged 18 to 90 years to determine if a set of individual-difference variables--vocabulary, education, depression, gender, marital status, and employment status--mediates the effects of aging on a wide range of laboratory-analogue tests of everyday memory. The data indicated that age was consistently the most significant predictor of memory performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
88
3
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 39 publications
(61 reference statements)
9
88
3
2
Order By: Relevance
“…Physical health could also be important, given a link between poorer health status and lower cognitive functioning (e.g., Hultsch, MacDonald, Hunter, Levy-Bencheton, & Strauss, 2000). Depending on the cognitive task, gender differences could also play a role (e.g., Larrabee & Crook, 1993;West, Crook, & Barron, 1992). Because of the well-documented age differences in many cognitive measures (e.g., Salthouse, 1996), there could be age differences in memory failures.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Physical health could also be important, given a link between poorer health status and lower cognitive functioning (e.g., Hultsch, MacDonald, Hunter, Levy-Bencheton, & Strauss, 2000). Depending on the cognitive task, gender differences could also play a role (e.g., Larrabee & Crook, 1993;West, Crook, & Barron, 1992). Because of the well-documented age differences in many cognitive measures (e.g., Salthouse, 1996), there could be age differences in memory failures.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…For instance, West, Crook, and Barron (1992) reported that verbal ability, a measure of crystallized ability (Cattell, 1971), was the best predictor of performance on certain tests of everyday memory (i.e., memory for telephone number and news). With regard to the basic abilities associated with the broad fluid domain (Cattell, 1971), Kirasic, Allen, Dobson, and Binder (1996) reported that working memory was the strongest predictor of individual differences on a set of measures assessing declarative learning for information from everyday stimuli (i.e., a bus schedule, a map, and a menu).…”
mentioning
confidence: 99%
“…Recent studies reporting gender differences in episodic memory are listed in Table 1. The majority of these studies come from research on adult age differences in memory (Hill et a1., 1995;Hultsch, Masson, & Small, 1991;Larrabee & Crook, 1993;Rabbitt, Donlan, Watson, McInnes, & Bent, 1995;Schaie & Willis, 1993;West, Crook, & Barron, 1992;Zelinski, Gilewski, & Schaie, 1993), but gender differences have also been reported in studies done to evaluate or establish norms for memory tests (Bolla- Wilson & Bleecker, 1986;Geffen, Moar, O'Hanlon, Clark, & Geffen, 1990;Ruff, Light, & Quayhagen, 1988;Temple & Cornish, 1993). Although most episodic memory research has involved verbal materials, gender differences in episodic memory have also been found with the use of other types of materials, such as faces (Hill et aI., 1995;McKelvie, Standing, St. Jean, & Law, 1993;Wahlin et aI., 1993), pictures (Galea & Kimura, 1993), locations (Eals & Silverman, 1994;Hill et aI., 1995), and odors (Lehmer, 1993).…”
mentioning
confidence: 99%